Buyer-side gender discrimination in bargaining: Evidence from seed sales in Uganda - Van Campenhout, Bjorn; Nabwire, Leocardia (Elsevier, 2025)
Haggling over prices is a common feature of economic transactions in many societies. This study examines whether the gender of the seller influences buyers’ negotiation strategies and outcomes in bilateral price bargaining. Using a bargaining experiment in eastern Uganda, we analyze interactions between smallholder maize farmers and either a male or female seed seller. Our findings reveal that buyers negotiating with female sellers are less likely to accept the initial offer price and respond with lower counter-bids compared to those bargaining with male sellers. Negotiations also last, on average, one round longer when the seller is a woman, and final transaction prices are nearly 9 percent lower. These results are particularly relevant for rural economies, where restrictive gender norms limit women’s financial autonomy. Given that small agribusinesses often provide one of the few viable income-generating opportunities for women, gender biases in market interactions can have substantial implications for economic empowerment and household welfare.